The promotion of oral health within Health Promoting Schools in KwaZulu-Natal - M Reddy; S Singh (South African Medical Association, 2017)
Background. Oral health promotion is a cost-effective strategy that can be implemented at schools for the prevention of oral diseases. Theimportance and value of school-based interventions in children has been identified in South Africa (SA). Although oral health strategiesinclude integrated school-based interventions, there is a lack of published evidence on whether these strategies have been translated intopractice and whether these programmes have been evaluated.Objective. To assess the efficiency and sustainability of the toothbrushing programme implemented at health-promoting schools inKwaZulu-Natal Province, SA.Methods. A mixed-methods approach was used for this study, conducted at 23 health-promoting schools in KwaZulu-Natal using focusgroup discussions. Triangulation was used for evaluation.Results. The intervention implemented had created awareness of oral health for learners, educators and parents. Findings in this studyindicate that although there were benefits obtained from this school-based intervention, many challenges, such as time constraints, largeclasses and a lack of adequate resources and funding, affected the sustainability of the programme.Conclusion.The school setting has the potential to deliver integrated preventive and promotive programmes provided they are supportedby adequate funding and resources.